Crater Blasting Method Applied to Pillar Recovery at Falconbridge Nickel Mines Ltd.* - C. J. Monahan (Society for Mining, Metallurgy & Exploration, 1982)
INTRODUCTION With the introduction of large diameter hole drilling to underground mining, a need for the development and utilization of new blasting technology has arisen. This new technology has resulted in more efficient blasting and in easier and cheaper mining. The application of spherical charges to the crater blasting method is an im¬portant part of this technology. Spherical charges, or their geometric equivalent, make for highly efficient use of explosives in the cratering application. Their geo¬metrical configuration, normally a length :diameter ra¬tio of <6:1, limits their charge weight size. For exam¬ple in a 165-mm (61/2-in.) hole a spherical charge weighs approximately 34 kg (75 lb). These dimensional and weight restrictions require careful engineering design and control in the production application. Strathcona mine, a large tonnage mechanized cut¬and-fill and blasthole stoping operation located on the north rim of the Sudbury Basin, has successfully em¬ployed the crater blasting method in production blasting for the past two and a half years (as of 1979). As a result, this method, using spherical charges, has made possible the development and implementation of a verti¬cal retreat blasthole mining method which is being used for rib pillar recovery. The crater method used at Strathcona essentially in¬volves blasting off horizontal slices of ore into an under¬cut while retreating vertically to the pillar overcut elevation. Loading and priming of the holes is achieved from the overcut and the blasted muck is recovered by load¬haul-dump (LHD) units through a drawpoint system. Valuable experience on the behavior and performance of explosives in large diameter holes has been gained in both the operating and engineering fields from the appli¬cation of this blasting method. It has been used in drop raising and is currently being evaluated for use in pri¬mary stoping operations. Also, serious consideration is being given to its use for the recovery of post pillars in mined-out and backfilled cut and fill stopes. The method has significant advantages over conven¬tional methods of pillar recovery from economic, ground control, and safety points of view. These include cost benefits due to a minimum stoping development, less ground support, reduced labor requirements, and faster mining rate. Research on the blasting mechanism indi¬cated the method should result in less damage to fill walls than would be normally expected with conven¬tional longhole or large diameter hole cylindrical blast¬ing (benching). This is primarily due to the limited charge weight per delay because of the size dimensions of a spherical as compared with a cylindrical charge and also because the large diameter holes experience less de¬viation than standard-sized longholes. Experience has shown that wall damage has been minimized with the use of this method. The safety aspects of the working environment are also improved as there is no require¬ment for manpower to go under exposed backs after blasting, which is a significant improvement over the cut-and-fill method. CRATERING THEORY General The term cratering, in blasting, is applied to the for¬mation of a surface cavity in a material as the result of detonating an explosive charge in that material. This blasting concept was initially used as a tool in the eval¬uation of explosives performance; however, it has been utilized more recently on surface and to a lesser extent in underground blasting operations. Explosive charges used in crater method are nor¬mally spherical or the geometric equivalent, as research into the application of this breakage mechanism to rock indicates that spherical charges or their equivalent pro¬duce optimum results. In blasting practice, spherical charges have been defined as having a length to diameter (L: D) ratio of 4:1 or less, and up to, but not exceeding a L: D = 6:1. Thus, for holes 165 mm (61/2 in.) diam, a charge 165 mm (61/2 in.) diam, and 990 mm (39 in.) in length would constitute a spherical charge. Crater Testing Crater testing for underground application is nor¬mally accomplished by drilling smaller than production sized horizontal holes into drift walls, placing relatively small charges of explosives in the holes at various depths of burial, firing the charges, and measuring the results. The results are scaled to develop charge weight size and depth of burial parameters for production hole sizes. In theory, this procedure is valid and is appli¬cable for surface blasting; however, in underground applications where the craters are inverted, there is some question as to whether extrapolation of the test results is appropriate. As well as the fact that craters are in¬verted with resultant gravity stresses, testing is often done in a waste rock drift where the properties differ from those in ore rock. There is also some question as to whether a 51 or 76-mm (2 or 3-in.) diam charge behaves similarly to a 165-mm (61/2-in.) charge in a confined borehole. Crater testing at Strathcona involved drilling 76-mm (3-in.) diam holes at various depths ranging from 1 to 3 m (3 to 10 ft). The test holes were drilled in the wall of a predominately waste drift as well as in a stope wall. Charges were placed at various depths of burial, were confined, fired, and the results measured. Although the results were somewhat erratic, possibly because of the aforementioned reasons, they did provide guidelines for basic design for production application. MINING METHOD APPLICATION FOR PILLAR RECOVERY Following initial crater testing, assessment, and tech¬nical evaluation, it was decided to use this blasting tech¬nique in a production application, and to incorporate